2019
DOI: 10.1177/0748233719871778
|View full text |Cite
|
Sign up to set email alerts
|

Ambient fine particulate matter induces inflammatory responses of vascular endothelial cells through activating TLR-mediated pathway

Abstract: This study aims to investigate the role of Toll-like receptors (TLRs) on fine particulate matter (PM2.5)-induced inflammatory responses of vascular endothelial cells. Inflammatory factors and TLRs were examined in the aorta of mice after nonsurgical intratracheal instillation of PM2.5 as well as in the human umbilical vein endothelial cells (HUVECs) treated with PM2.5. In addition, the effects of TLR2 and TLR4 inhibitors in the secretion of interleukin 6 (IL-6) and IL-1β and the expression of TLRs were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…Further studies revealed that PM 2.5 activates the NF‐κB pathway through Toll‐like receptors (TLRs) on the surface of lung macrophages, such as TLR2 or TLR4, which upregulate the release of inflammatory cytokines (Prueitt, Cohen, & Goodman, 2015; Van et al, 2001). PM 2.5 can also be identified by TLRs and has also been verified in HUVECs (Le et al, 2019). Besides, PM 2.5 ‐mediated ROS can also indirectly induce inflammation.…”
Section: Underlying Mechanisms Of Pm25‐induced Asmentioning
confidence: 84%
“…Further studies revealed that PM 2.5 activates the NF‐κB pathway through Toll‐like receptors (TLRs) on the surface of lung macrophages, such as TLR2 or TLR4, which upregulate the release of inflammatory cytokines (Prueitt, Cohen, & Goodman, 2015; Van et al, 2001). PM 2.5 can also be identified by TLRs and has also been verified in HUVECs (Le et al, 2019). Besides, PM 2.5 ‐mediated ROS can also indirectly induce inflammation.…”
Section: Underlying Mechanisms Of Pm25‐induced Asmentioning
confidence: 84%
“…TLR4/NADPH oxidase-dependent mechanisms are presumed to be involved (Kampfrath et al, 2011 ; Woodward et al, 2017 ). Activation of TLR2/NF-kB has also been demonstrated, both in vascular endothelial cells (Le et al, 2019 ) and in neuronal cells (Tian et al, 2021 ). In general, the TLR signaling activation results in the production of inflammatory cytokines and interferons (type 1) that occurs through a MyD88-dependent and interleukin-1 receptor (TRIF)-dependent pathways.…”
Section: Routes Of Pm Entering and Affecting The Brainmentioning
confidence: 97%
“…A previous study reported that PM2.5 increased the expression of TLR2 and TLR4 and promoted the secretion of inflammatory factors IL‐1β and IL‐6 in the aorta of mice as well as in the HUVECs. On the other hand, the suppression of TLR2 or TLR4 reduced the secretion of IL‐1β and IL‐6 (Le et al, 2019), suggesting that both TLR2 and TLR4 were involved in vascular inflammatory responses induced by PM2.5. Based on the above studies, PM2.5 triggers inflammation of VECs and then induces VECs activation via inflammatory signal pathway such as ERK/AKT/NF‐κB and COX‐2/mPGES‐1/PGE2.…”
Section: Pathophysiological Mechanisms Of Pm25‐induced Damage Of Vecsmentioning
confidence: 99%